Another Lost Decade? Effects of the Financial Crisis on Project Finance for Infrastructure - Leigland, James (World Bank, Washington, DC, 2012)
Rapid growth in project finance, driven by huge increases in liquidity, helped fuel the gains in private participation in infrastructure (PPI) in developing countries in the past decade. But when the financial crisis hit, the excess liquidity began to dry up as lenders backed away from practices that had helped generate it. The effects are already apparent in greater delays in financial closures, more cancellations, and higher financing costs for PPI projects. If full recovery of the project finance market takes much longer than expected, some of the measures that are now being adopted to avoid shutting down project pipelines might have unintended and very negative consequences.